Surviving the whiteboard interview : a developer's guide to using soft skills to get hired - Gant, William (Apress, 2019)
"The industry standard whiteboard interview can be daunting for developers. Let's face it: it combines the worst aspects of a typical interview, on-the-spot public speaking, a quiz show, and a dinner party full of strangers judging you--all at once. Brilliant developers can let their nerves get the best of them and completely bomb a whiteboard interview, while inexperienced developers who excel in soft skills can breeze through them. In Surviving the Whiteboard Interview, author William Gant uses his real-world knowledge and expertise to guide you through the psychological roadblocks of a coding test while also providing you with a sample coding challenge. With enough preparation, information, and assured confidence, you can survive a whiteboard interview at any organization. In addition to the benefits listed above, Gant helps you explore how you can create a good soft skills impression that will last beyond the whiteboard test by showing your work ethic, positive attitude, and ability to take and implement criticism effectively. These assets will unequivocally serve other parts of your life outside of an interview context, as well. While Gant does not promise that you will ever truly enjoy interviewing, he does promise to arm you with the proper preparation techniques and knowledge needed to tame the common fears and dread that come along with it. Maximize your career potential and get inspired with Surviving the Whiteboard Interview. The steps to your dream role just might be closer than you think."--Back cover